The Effect of Performance Appraisal and Job Satisfaction on Employee Performance at Bank Mandiri Taspen Manado Branch Office - Mawei, Anggely; Rumawas, Wehelmina; Asaloei, Sandra Ingried (Productivity, 2025)
Performance appraisal is the process of evaluating employee performance based on organizational standards and goals. An employee’s positive or negative feelings toward their job is called job satisfaction, which is influenced by working conditions, compensation, relationships with coworkers, and professional development opportunities. Fair and transparent appraisals can increase satisfaction, while high job satisfaction contributes to improved employee performance. Companies must be able to achieve competitive advantage by maximizing the performance of their employees in the current era of globalization and increasingly fierce business competition. The research objectives are: 1. To determine the effect of Performance Appraisal on Employee Performance of Bank Mandiri Taspen Manado Branch Office. 2. To determine the effect of Performance Appraisal on Job Satisfaction of employees of Bank Mandiri Taspen Manado Branch Office. 3. To determine the effect of Job Satisfaction on Employee Performance at Bank Mandiri Taspen Manado Branch Office. This research uses quantitative research. In statistical analysis of data using SEM PLS method. The results of this study indicate that Performance Appraisal has a positive and significant effect on Employee Performance of Bank Mandiri Taspen Manado Branch Office. Performance Appraisal has a positive and significant effect on Job Satisfaction at Bank Mandiri Taspen Manado Branch Office. Job satisfaction has no effect on Employee Performance of Bank Mandiri Taspen Manado Branch Office.